Akselerasi Digitalisasi Keuangan, Pemasaran, dan Kepatuhan Pajak bagi Pengrajin Rajut dan Kerancang untuk Mewujudkan Kemandirian Ekonomi Kreatif dalam Mendukung SDGs dan Asta Cita: Strengthening Financial Digitalization, Digital Branding, and Tax Literacy for the Rumah Bagonjong Handmade Craft MSME in Bukittinggi - Silmi Silmi; Verni Juita; Jefril Rahmadoni; Kevry Ramdany; Nadya Putri Nasha; Aidah Fikriyyah; Bunga Shafira (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2026)
Rumah Bagonjong Handmade, a micro, small, and medium-sized enterprise (MSME) in Bukittinggi City, Indonesia, faces challenges in business management, particularly in financial record-keeping, tax compliance, and brand identity, which limit its competitiveness in the digital economy. This community engagement program aimed to strengthen the enterprise’s managerial capacity through training and mentoring in digital financial management using the Sistem Informasi Aplikasi Pencatatan Informasi Keuangan (SIAPIK), tax administration, and branding development. Implemented from September to November 2025, the program consisted of four stages: needs assessment, two intensive training sessions, on-site implementation mentoring, and periodic monitoring and evaluation. The intervention resulted in significant improvements in business management capacity. The enterprise successfully transitioned from manual bookkeeping to digital financial recording using the SIAPIK application, enabling the independent preparation of monthly balance sheets and income statements. Tax literacy also improved, particularly regarding the regulations and calculation procedures for the 0.5% final income tax scheme applicable to MSMEs. In the marketing domain, the program transformed the enterprise’s social media into an active promotional platform through the adoption of a new visual brand identity that reflects the uniqueness of local products and the development of independently managed digital content. To ensure the sustainability of program outcomes, strategic production equipment including an overlock machine, a computerized embroidery machine, a cutting table, and a multifunction sewing machine was provided. These assets contributed to improved production capacity, operational efficiency, and the long-term sustainability of the enterprise.